“To find God in all things”: the meeting of faith and mathematics in Jesuit education during the scientific revolution - Araújo, Daniel Ferreira (História da Ciência e Ensino: construindo interfaces, 2021)
Resumo É bem conhecido e aceito que o início da tradição matemática dos jesuítas se deve a Christopher Clavius, professor de Matemática no Colégio Romano entre 1567 e 1595. Neste artigo, questiona-se: Quais eram os aspectos sociais, políticos, filosóficos, e as razões religiosas que levaram Clavius a criar um currículo educacional inovador que incluiu o ensino de matemática nas faculdades jesuítas? Para responder à esta pergunta, olhamos para os primeiros anos da Companhia de Jesus considerando o contexto histórico e uma análise de como o aprendizado matemático interagiu com a doutrina Católica. Palavras-chave: Pedagogia Jesuítica; Ciência e Fé; Igreja e ciência Abstract It is well known and accepted that the beginning of the mathematical tradition of the Jesuits is due to Christopher Clavius, professor of Mathematics in the Roman College between 1567 and 1595. In this article, the question is: What were the social, political, philosophical, and religious reasons that lead Clavius to create an innovative educational curriculum that included the teaching of mathematics in the Jesuit colleges? To answer this question, we look at the early years of the Society of Jesus considering the historical context and an analysis of how mathematic learning interacted with the Catholic doctrine. Keywords: Jesuit pedagogy; science and faith; Church and science